Pengaruh Penerapan Manajemen Mutu ISO 9001:2008 Dan Kepemimpinan Terhadap Kualitas Pelayanan SMK Negeri 2 Kabupaten Tangerang - Danang Rifai; Syamsul Fallah; Mira Purwasari (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2018)
This research entitled the influence of the implementation of ISO 9001:2008 quality management on leadership and service quality in SMK Negeri 2 Kabupaten Tangerang. The formulation of this research problem is whether there is influence of the implementation of ISO 9001: 2008 and principal leadership on the quality of service in SMK Negeri 2 Tangerang Regency. While tujuaannya is wanted to know the effect of the implementation of ISO 9001: 2008 and teacher performance on service quality in SMK Negeri 2 Kabupaten Tangerang. This research used survey method with correlation technique, sample size 350 people, student research object, teacher and employee of SMK Negeri 2 Kabupaten Tangerang. The result of this research is that there is a significant effect of quality management of ISO 9001: 2008 and principal leadership together towards the quality of service in SMK Negeri 2 Kabupaten Tangerang. This is evidenced by (sig) of 0.000 <0.05 and Fcount of 62.233. There is a significant effect of quality management of ISO 9001: 2008 on the quality of service in SMK Negeri 2 Kabupaten Tangerang. This is evidenced by the value of Sig = 0.000 <0.05 and tcount = 5.933. There is a significant influence of Headmaster's leadership on the quality of service in SMK Negeri 2 Kabupaten Tangerang. And proved by the value of Sig = 0.001 <0.05 and tcount = 3.396.